1996
DOI: 10.1523/jneurosci.16-03-01101.1996
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in shaking-B prevent electrical synapse formation in the Drosophila giant fiber system

Abstract: The giant fiber system (GFS) is a simple network of neurons that mediates visually elicited escape behavior in Drosophila. The giant fiber (GF), the major component of the system, is a large, descending interneuron that relays visual stimuli to the motoneurons that innervate the tergotrochanteral jump muscle (TTM) and dorsal longitudinal flight muscles (DLMs). Mutations in the neural transcript from the shaking-B locus abolish the behavioral response by disrupting transmission at some electrical synapses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
164
0
23

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 10 publications
10
164
0
23
Order By: Relevance
“…8), as shown with unilateral antennal backfill using TMR-DA, which resulted in a lower level of contralateral staining with respect to NB. The contralateral staining observed in the case of NB could be due to the presence of gap junctions that might couple projections of ORNs among different glomeruli: in fact, gap junctions are permeable to the small NB molecules (MW 287) (Phelan et al 1996;Haag and Borst 2005;Anava et al 2009), but not to the ten times larger TMR-DA molecules (MW 3000). This hypothesis seems to be confirmed by the fact that, after staining the contralateral AL, the NB tracer proceeds to be incorporated also in the contralateral antennal nerve, which is not the case of unilateral TMR-DA backfills.…”
Section: Neural Projections From the Antennal Nervementioning
confidence: 99%
“…8), as shown with unilateral antennal backfill using TMR-DA, which resulted in a lower level of contralateral staining with respect to NB. The contralateral staining observed in the case of NB could be due to the presence of gap junctions that might couple projections of ORNs among different glomeruli: in fact, gap junctions are permeable to the small NB molecules (MW 287) (Phelan et al 1996;Haag and Borst 2005;Anava et al 2009), but not to the ten times larger TMR-DA molecules (MW 3000). This hypothesis seems to be confirmed by the fact that, after staining the contralateral AL, the NB tracer proceeds to be incorporated also in the contralateral antennal nerve, which is not the case of unilateral TMR-DA backfills.…”
Section: Neural Projections From the Antennal Nervementioning
confidence: 99%
“…Genome sequencing projects identified eight innexin genes in the fruit fly Drosophila, however, only a few mutants exist that have been molecularly and functionally characterized. It has been shown that innexin1 (ogre) and innexin8 (shakingB) are involved in the physiology of the giant fibre and the adult visual systems (Watanabe and Kankel 1990;Curtin et al 2002;Krishnan et al 1993;Phelan et al 1996Phelan et al , 2005Shimohigashi and Meinertzhagen 1998;Zhang et al 1999;Jacobs et al 2000); innexin4 (zero population growth) controls germ cell differentiation (Tazuke et al 2002;Gilboa et al 2003) and we have recently shown that during foregut morphogenesis, innexin2 is a Wingless/WNT target gene that coordinates epithelial morphogenesis . Mutants for innexin2 (kropf), which lack both their maternal and zygotic innexin2 contributions fail to develop any epithelial tissues, and overexpression of innexin2 in the epidermis results in multilayering and irregular cell shapes suggesting that innexin2 is a key factor to control epithelial organization during morphogenesis of tissues and organs in the body (Bauer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical synapse defects occur in shak-B mutants in the interneurons connected to the optic nerve and giant nerve systems; thus, shak-B was predicted as the gene of gap junction proteins in fruit flies (Phelan et al, 1996). A similar protein family found in fruit flies and nematodes was named innexin (INvertebrate conEXIN) (Phelan et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%